2013
DOI: 10.3390/ijgi2041015
|View full text |Cite
|
Sign up to set email alerts
|

User Experience Design in Professional Map-Based Geo-Portals

Abstract: Abstract:We have recently been witnessing the growing establishment of map-centered web-based geo-portals on national, regional and local levels. However, a particular issue with these geo-portals is that each instance has been implemented in different ways in terms of design, usability, functionality, interaction possibilities, map size and symbologies. In this paper, we try to tackle these shortcomings by analyzing and formalizing the requirements for map-based geo-portals in a user experience based approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…Studies on WebGIS or web map sites are often more complex, e.g., more test persons are interviewed or more detailed evaluation results are provided, than studies with geoportals, which often focus on data search. Some findings of these studies can still be found in available web applications: lack of clarity in user interface (UI) structures, insufficient map sizes, and interactions, e.g., missing map functions or unstructured toolbars, and inconsistent terminology [9][10][11][12][13][14][15]. In GI web applications, several usability problems exist, which can be detected easily and occur frequently.…”
Section: Related Workmentioning
confidence: 99%
“…Studies on WebGIS or web map sites are often more complex, e.g., more test persons are interviewed or more detailed evaluation results are provided, than studies with geoportals, which often focus on data search. Some findings of these studies can still be found in available web applications: lack of clarity in user interface (UI) structures, insufficient map sizes, and interactions, e.g., missing map functions or unstructured toolbars, and inconsistent terminology [9][10][11][12][13][14][15]. In GI web applications, several usability problems exist, which can be detected easily and occur frequently.…”
Section: Related Workmentioning
confidence: 99%
“…By further exploring the high degree centrality papers, we can determine that in cluster 1, the usability metric is mainly used for traditional cartography problems, for example, Ooms [62] proposed an improved label placement method based on eye movement analysis; Golebiowska [63] integrated usability metric to explore how map legend works as map is read; or using the Visual Analytics Toolkit for complementing conventional eye movement data analysis method [64]. In cluster 2, the usability research achievements are mainly related to new and emerging technologies like web mapping navigation schemes [20], citizen-based web mapping [65], mobile phone or tablet [66], or user experience in map-based geo-portals [67]. An examination of other clusters also reveals some interesting research topics, such as studies of perception of 2D and 3D terrain visualization [68], difference of experts and novices attentive behavior [12,13], animated maps [15,16], image enhancement in web mapping [69], and volunteered geographic information (VGI) [19].…”
Section: Research Theme Clustersmentioning
confidence: 99%
“…Alternately, a geo-portal is a web-based system that allows users to discover particular geo-datasets by looking into the associated metadata, to portray the data on a map, and to retrieve the data in adequate formats to further process them in a professional workflow. (Resch andZimmer, 2013: 1019) These sites have not traditionally integrated Volunteered Geographic Information (VGI), though VGI sites attract millions of users across the world (e.g., openstreetmap.org). As Bugs et al (2010: 173) describe: "In general, users can post comments on a map, but user-friendly, map-based citizen's opinion and interactive discussion is still not widely supported."…”
Section: Terminologymentioning
confidence: 99%
“…Other papers tested whether paper-based or electronic PPGIS produced a higher participation rate (Brown, 2012;Pocewicz et al, 2012) and whether electronic PPGIS introduces a sampling bias Brown et al, 2013). Additionally, a smaller literature (e.g., Harrie et al, 2011;Resch and Zimmer, 2013) discusses technical advancements in the field and efforts to standardize data portals (particularly in Europe), though much of this work has been confined to web development forums.…”
Section: Applicationsmentioning
confidence: 99%